Neonatal Graves’ disease from high maternal TRAB antibody levels despite definitive therapy - Dalal S. Ali; Maisa H. Al Kiyumi; Abdulrahman Almoulia; Rachel K. Crowley; Medina Mohamed (Journal of Clinical and Translational Endocrinology Case Reports)
Background: Graves’ disease is an autoimmune thyroid disorder that poses significant risks during pregnancy, affecting both the mother and fetus. Case presentation: We present four cases of neonatal Graves' disease arising in the offspring of two women treated for Graves' disease, highlighting the disease's transient but potentially severe impact on newborns. In the first case, the pregnant woman underwent a total thyroidectomy during the second trimester, whereas in the second case, the patient had Graves' disease and was treated with radioactive iodine six years prior. Both women demonstrated a very high level of thyrotropin receptor antibodies (TRAb) during pregnancy. Discussion: These cases underline the necessity of vigilant monitoring of TRAb levels in pregnant women with a history of Graves' disease, regardless of previous treatment or current euthyroid status. This approach aims to facilitate early detection and treatment of neonatal Graves’ disease, mitigating its impact on growth and development. Conclusion: Our findings support recommendations for baseline and mid-gestation TRAb testing in this population, as well as immediate postnatal testing for neonates born to mothers with active or inactive Graves’ disease.